Knockdown of BmTCP-1β Delays BmNPV Infection in vitro - Wang, Xue-yang; Shao, Zuo-min; Chen, Qian-ying; Xu, Jia-ping; Sun, Xia; Xu, Zhen-ping; Li, Mu-wang; Wu, Yang-chun (Frontiers in Microbiology, 2019)
The molecular mechanism of silkworm resistance to Bombyx mori nucleopolyhedrovirus (BmNPV) infection remains unclear. The chaperonin containing t-complex polypeptide 1 (TCP-1) is essential for the folding of tubulin and actin to produce stable and functional competent protein conformation. However, little is known about this protein in silkworm. In the present study, a gene encoding the TCP-1β protein in silkworm was characterized, which has an open reading fragment of 1,611 bp encoding a predicted 536 amino acid residue-protein with a molecular weight of approximately 57.6 kDa containing a Cpn60_TCP1 functional domain. The sequence conservation is 81.52%. The highest level of BmTCP-1β mRNA expression was found in the midgut, while the lowest was in the hemolymph. To further study the function of BmTCP-1β, expression was knocked down with siRNA in vitro, resulting in significant downregulation of the selected cytoskeletal-related genes, actin and tubulin, which was also confirmed by overexpression of BmTCP-1β in BmN cells using the pIZT/V5-His-mCherry insect vector. Moreover, knockdown of BmTCP-1β significantly prolonged the infection process of BmNPV in BmN cells, which was also verified by overexpression of BmTCP-1β in BmN cells. Based on the results of the present study, we concluded that BmTCP-1β plays a vital role in BmNPV infection by regulating the expression of tubulin and actin. Taken together, our work provides valuable data for the clarification of the molecular mechanism of silkworm resistance to BmNPV infection.